Immunological Aspects of Persistent Hepatitis B in Children - Harsoyo Notoatmojo (Paediatrica Indonesiana, 1998)
We studied the immunological status of 203 children having persistent Hepatitis B (positive HBsAg) ranging in age from 6 to 14 years in Semarang Municipality. All patients showed negative results of humoral immunity (IgM anti-HBc), excluding the possibility of acute hepatitis B (HB). Cellular immunity examination using CMI skin test showed positive result in 64.9% of persistent and 65.2%, ln non-persistent HB (p>0.05). T cell examination shows significant statistical difference (p<0.01) between persistent and non-persistent HB, and there was a significant difference (p<0.01) on CD4 cell examination; indicating a difference on immunoregulation function and response repression of anti-virus between the two groups. There was no significant differences on CD4/CD8 ratio between persistent and non-persistent HB. The specific function of cytotoxic T cell also shows no significant difference between the two groups.